Hybrid far infrared radiation and hot air rice grain dryer. - John CarlosC. Mislang, Leidi Naces, Grazelle R. nadel, Arl Dominic C. Que. 4 0 16; 5
u
Undergraduate Thesis : (Bachelor of Science in Electronic Engineering) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2